The APA Style 7th Edition (2020): some notable changes / Ho Chui Chui - Ho, Chui Chui (Universiti Teknologi MARA, Kedah, 2020)
The latest version of the American Psychological Association publication manual has been recently introduced to replace the sixth edition which was published in 2010. Students, educators and writers are expected to fully adopt the new guidelines by the middle of 2020. This paper highlights the important changes to note particularly regarding in-text citations and references. The differences between APA 6 and APA 7 are illustrated with pertinent examples.